Who Wrote the Lunenburg Letter? The Untold Story of the "Conscientious Sister" of Lunenburg - Matson, David Lertis (Stone-Campbell journal, 2008)
The "Lunenburg Letter" is arguably the most famous piece of correspondence in the history of the Stone-Campbell Restoration Movement. With it the author unleashed a theological firestorm that would engulf Alexander Campbell in the flames of a baptismal controversy whose embers continue to smolder down to the present day. Who was the "conscientious sister" who lit the fuse? This article seeks to shine some light on a woman whose identity has been shrouded in mystery from the very beginninguntil now.